A specific and rapid method for detecting Bacillus and Acinetobacter species in Daqu - Wei, Yanwei; Zhang, Shuyue; Guan, Guikun; Wan, Ziran; Wang, Ruiming; Li, Piwu; Liu, Yu; Wang, Junqing; Jiao, Guanhua; Wang, Hao; Sun, Chuying (Frontiers in Bioengineering and Biotechnology, 2023)
Daqu is a spontaneous, solid-state cereal fermentation product used for saccharification and as a starter culture for Chinese Baijiu production. Bacillus and Acinetobacter, two dominant microbial genera in Daqu, produce enzymes and organic acids that influence the Daqu quality. However, there are no rapid analytical methods for detecting Bacillus and Acinetobacter. We designed primers specific to the genera Bacillus and Acinetobacter to perform genetic comparisons using the 16S rRNA. After amplification of polymerase chain reaction using specific primers, high-throughput sequencing was performed to detect strains of Bacillus and Acinetobacter. The results showed that the effective amplification rates for Bacillus and Acinetobacter in Daqu were 86.92 and 79.75%, respectively. Thus, we have devised and assessed a method to accurately identify the species associated with Bacillus and Acinetobacter in Daqu, which can also hold significance for bacterial typing and identification.